Immigration and Gender Differences in the Labor Market - Joan Llull (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
This paper analyzes the effect of immigration on gender gaps in the labor market. Using an equilibrium structural model for the U.S. economy, I simulate the importance of two mechanisms: the differential labor market competition induced by immigration on male and female workers, and the availability of cheaper child care services. Consistent with the literature, aggregate effects on gender and participation gaps are negligible. However, female are more negatively affected by labor market competition, even though these effects are compensated from the cheaper-childcare effect. This generates heterogeneity in the effects along the skill distribution: gender gaps are increased at the bottom of the distribution and reduced at the top. Human capital adjustments are also heterogeneous.
Keywords: J16; J2; J31; J61; 330; Gender Gaps; Immigration; Human Capital; Child-care Cost; Competition; Equilibrium